Community-Based Services for Child Survivors of Sexual Violence - As’ad, Muh.; Nasir, Sudirman; Suriah, Suriah; Riskiyani, Shanti; Stang, Stang; Balqis, Balqis; Mallongi, Anwar (Journal of Neonatal Surgery, 2025)
Background: Sexual violence against children is a complicated social problem that has psychological and social consequences for victims. A community-based approach to safeguarding and supporting children who have experienced sexual assault is the provision of refuge. Objective: The purpose of this study is to examine how shelters in Makassar City handle cases of sexual abuse against children, taking into account the services' efficacy, difficulties encountered, and effects on survivors and the community. Method: This research employs a case study methodology in conjunction with a qualitative approach. Data were collected through in-depth interviews, observations, and document reviews. Nine individuals served as research informants, including survivors of childhood, members of the Shelter, survivor families, and representatives of associated organizations. Results: Shelters play a major role in assisting, preventing, and educating children about sexual violence. Shelters not only offer protection but also play a crucial role in facilitating legal processes, supporting psychosocial recovery, and providing education on positive parenting within the community. Nonetheless, difficulties in inter-agency coordination and the lack of long-term monitoring continue to pose significant barriers to the effectiveness of services. Conclusion: Shelters play a crucial role in tackling sexual violence against children by employing a community-based strategy. Improved inter-agency coordination and long-term monitoring of survivors are needed to ensure sustainable recovery.